Evans Syndrome in Children: Long-Term Outcome in a Prospective French National Observational Cohort - Aladjidi, Nathalie; Fernandes, Helder; Leblanc, Thierry; Vareliette, Amélie; Rieux-Laucat, Frédéric; Bertrand, Yves; Chambost, Hervé; Pasquet, Marlène; Mazingue, Françoise; Guitton, Corinne; Pellier, Isabelle; Roqueplan-Bellmann, Françoise; et al. (Frontiers in Pediatrics, 2015)
Evans syndrome (ES) is a rare autoimmune disorder whose long-term follow-up characteristics are unknown. Patients under 18 at the time of diagnosis of a first autoimmune cytopenia have been included since 2004 in a national prospective observational cohort. In 2014, 156 children diagnosed between 1981 and 2014 with ES, were analyzed. The median age at initial cytopenia was 5.4 (0.2-17.2) years old. For 85 sequential cases, the median delay between the episodes of AIHA and ITP was 2.4 years (0.1–16.3). The median follow-up since ES diagnosis was 6.5 years (0.1-28.8). ES revealed underlying diseases in 10% of children; in 60% of patients, various associated immune manifestations were observed, and ES remained primary in 30%. Five-year ITP and AIHA relapse-free survival were respectively 25% and 61%. In all, 69% of children required one or more than one second-line immune treatment and 15 patients (10%) died at a median age of 14.3 years (1.7-28.1). This national work provides the first consistent clinical description for ES and underscores the high percentage of associated immune manifestations, the long-term complications, and treatment toxicities. Current challenges include the identification of underlying genetic immune dysregulations and better characterization of subgroups of patients and of second-line therapy strategies.